Arab and Jew woundad spirits in a promised land - Shipler, David K. 1942- (Penguin Books, 2002)
The Jew, according to the Arab stereotype, is a brutal, violent coward; the Arab, to the prejudiced Jew, is a primitive creature of animal vengeance and cruel desires. In this monumental work, David Shipler delves into the origins of the prejudices that have been intensified by war, terrorism, nationalism, and the failure of the peace process.